Vulnerability of the Asian Typical Steppe to Grazing and Climate Change - Christensen, Lindsey; Coughenour, Michael B.; Ellis, James E.; Chen, Zuo Zhong (Climatic change, 2004)
The vulnerability of grassland vegetation in Inner Mongolia to climate change and grazing was examined using an ecosystem model. Grazing is an important form of land use in this region, yet there are uncertainties as to how it will be affected by climate change. A sensitivity analysis was conducted to study the effects of increased minimum and maximum temperatures, ambient and elevated CO2, increased or decreased precipitation, and grazing on vegetation production. Simulations showed that herbaceous above ground net primary production was most sensitive to changes in precipitation levels. Combinations of increased precipitation, temperature, and CO2 had synergistic effects on herbaceous production, however drastic increases in these climate scenarios left the system vulnerable to shifts from herbaceous to shrub-dominated vegetation when grazed. Reduced precipitation had a negative effect on vegetation growth rates, thus herbaceous growth was not sustainable with moderate grazing. Shifts in temporal biomass patterns due to changed climate have potentially significant implications for grazing management, which will need to be altered under changing climate to maintain system stability. [PUBLICATION ABSTRACT]